Gaucher disease epidemiology and natural history: a comprehensive review of the literature. Issue 2 (7th February 2017) - Nalysnyk, Luba; Rotella, Philip; Simeone, Jason C.; Hamed, Alaa; Weinreb, Neal
ABSTRACT: Objectives: The objectives of this research were: (1) to heighten awareness of Gaucher disease (GD), a rare lysosomal storage disorder with highly heterogeneous patterns of organ involvement and disease severity, to clinicians most likely to encounter these patients, and; (2) to summarize the published evidence on GD epidemiology which is essential to accurately depict the total societal burden of this rare worldwide disorder. Methods: A comprehensive literature review was undertaken to summarize the published evidence on the epidemiology of GD. MEDLINE, EMBASE, CENTRAL, and 'grey' literature sources published in English between January 1990 and March 2015 were searched to identify relevant publications. Results: In total, 188 full-text articles were reviewed and findings from 49 studies are summarized herein. The standardized birth incidence of GD in the general population varied from 0.39 to 5.80 per 100 000, and prevalence ranged from 0.70 to 1.75 per 100 000, respectively. Time from onset of GD symptoms to clinical diagnosis was highly variable, with median delays of up to 7 years reported. Discussion: The incidence and prevalence of GD is substantially higher among the Ashkenazi Jewish population than the general population. Limited epidemiologic information was available from Latin America, Africa, Asia, and developed nations such as the United States, Germany, and the United Kingdom. Conclusions: Signs and symptoms of GD frequently mimic more common hematologic conditions resulting in missed or delayed diagnosis. Early diagnosis and prompt initiation of treatment when indicated is crucial to prevent or minimize life-altering or life-threatening liver and skeletal complications.